1991
DOI: 10.1154/s0376030800009290
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Dislocation Densities in Hexagonal Close-Packed Metals using X-Ray Diffraction and Transmission Electron Microscopy

Abstract: X-ray diffraction (XRD) line-broadening analysis has been used to determine dislocation densities in zirconium alloys with hexagonal closepacked (hep) crystal structures and a complex distribution of dislocations reflecting the plastic, anisotropy of the material. The validity of the technique has been assessed by comparison with direct measurements of dislocation densities in deformed polycrystalline and neutron-irradiated single crystal material using transmission electron microscopy (TEM). The results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…The dislocation density q can be estimated based on the results of domain size and microstrain from the relation [25] q / e 2 lnð0:05D v Þ ð7Þ…”
Section: Xrd Analysismentioning
confidence: 99%
“…The dislocation density q can be estimated based on the results of domain size and microstrain from the relation [25] q / e 2 lnð0:05D v Þ ð7Þ…”
Section: Xrd Analysismentioning
confidence: 99%
“…To estimate the value of ρ s , Equation (2) factor F takes a value of 1 when n is equal to 1 in Equation (1), ε is the microstrain, b is Burger's vector, and k is a constant with values between 2 and 25. Nevertheless, according to Griffiths et al [61], Equation (2) only applies in cubic crystal structures because it ignores the anisotropic nature of the hcp crystal structure [62,63]. For this reason, Griffiths et al adapted Williamson and Smallman's hcp crystal structure, proposing Equation (3).…”
Section: Determination Of Dislocation Density From Xrdmentioning
confidence: 99%
“…The texture was measured and the dislocation density estimated using X-ray diffraction [21,22]. The inverse pole figure in the normal direction of the foil indicated that the resolved fraction of basal plane normals in the foil normal direction was, typically, 0.74.…”
Section: Microstructure Of the Specimensmentioning
confidence: 99%